PERLINDUNGAN HUKUM TERHADAP UANG SIMPANAN NASABAH DI BANK GAGAL OLEH LEMBAGA PENJAMIN SIMPANAN (LPS) MENURUT UU NOMOR 10 TAHUN 1998 DAN UU NOMOR 24 TAHUN 2004 - I Putu Indra Prastika (University of Udayana, 2016)
The economic crisis of 1997-1998 is marked by the liquidation of 16 commercial banks which resulted the collapse of public confidence in the national banking institutions. To handle the crisis, the government issued several policies there are security for payment of all liabilities of the Bank and public deposits (blankit Guarantiee). The Deposit Insurance Agency (LPS) emerged as an independent agency that serves the banking guarantee customer’s deposits in Indonesia. In this research, there are two problems to be dissussed (1) what are the steps taken by the Deposit Insurance Agency (LPS) when a bank fails and how if LPS has a financial difficulties? (2) what does the authority of the Deposit Insurance Agency (LPS) in the completion and management of the Bank Failure? The method for in this research are the approach of legislation (Statutes Approach) and the comparative approach whereas the type of the research in this study is a normative legal research which is basically to compare and find the relationship the Deposit Insurance Agency is listed in Law No. 24 of 2004 concerning the Deposit Insurance Agency and the Law No. 10 of 1998 concerning about banking. The problems are discussed based on the government’s principles, that the government has a strong commitment to ensure the sustainability of LPS including maintain public confidence in the LPS. While one of the authority of the Deposit Insurance Agency (LPS) in the completion and management for the Bank Failure are with mastering and managing the assets and liabilities of the Bank Failure which is rescued. Krisis ekonomi pada tahun 1997-1998, ditandai dengan dilikuidasinya 16 Bank Umum yang mengakibatkan runtuhnya kepercayaan masyarakat terhadap lembaga perbankan nasional. Untuk mengatasi krisis yang terjadi, pemerintah mengeluarkan beberapa kebijakan diantaranya memberikan jaminan atas seluruh kewajiban pembayaran Bank termasuk simpanan masyarakat (Blankit Guarantiee). Lembaga Penjamin Simpanan (LPS) muncul sebagai lembaga independen yang berfungsi menjamin simpanan nasabah perbankan di Indonesia. Dalam penelitian ini terdapat dua permasalah yang akan dibahas (1) Langkah-langkah apa sajakah yang diambil Lembaga Penjamin Simpanan (LPS) bila sebuah Bank mengalami kegagalan dan bagaimana jika LPS mengalami kesulitan keuangan? (2) Apakah kewenangan Lembaga Penjamin Simpanan (LPS) dalam penyelesaian dan penanganan Bank gagal?. Metode pendekatan yang digunakan dalam penelitian ini adalah pendekatan peraturan perundang-undangan (Statutes Approach) dan pendekatan perbandingan (comperative approach) sedangkan tipe penelitian dalam penelitian ini adalah penelitian hukum normatif yang pada dasarnya untuk membandingkan dan mencari hubungan Lembaga Penjamin Simpanan yang terdapat dalam UU No. 24 Tahun 2004 tentang Lembaga Penjamin Simpanan dan UU No 10 Tahun 1998 tentang Perbankan. Dalam permasalahan ini pada prinsipnya Pemerintah mempunyai komitmen yang tinggi untuk menjaga keberlangsungan LPS termasuk menjaga kepercayaan masyarakat terhadap LPS. Sedangkan salah satu kewenangan Lembaga Penjamin Simpanan (LPS) dalam penyelesaian dan penanganan Bank gagal adalah dengan Menguasai dan mengelola asset dan kewajiban Bank gagal yang diselamatkan.